2021
DOI: 10.1155/2021/9830200
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplements Improve Blood Glucose and Insulin Resistance/Sensitivity among Healthy and GDM Pregnant Women: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Probiotic supplements may be seen as a promising way to improve glucose metabolism. This study aimed to evaluate the effects of probiotic supplements on blood glucose, insulin resistance/sensitivity, and prevention of gestational diabetes mellitus (GDM) among pregnant women. Methods. Eleven electronic databases were searched from inception to May 2020. Two authors independently identified randomized controlled trials (RCTs), assessed the eligibility and quality of the included studies, and then ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
1
13
1
1
Order By: Relevance
“…More encouragingly, probiotic supplements might be an assistant treatment strategy for these complications. A systematic review which included a total of 20 randomized controlled trials involving 2972 participants found that probiotic supplements had certain functions to reduce the level of fasting plasma glucose (FPG) and improve insulin, insulin resistance, and insulin sensitivity, especially for GDM and healthy pregnant women [13]. The long-term risk of growth-restricted fetuses is similar to that of offspring of women with GDM, and the role of insulin resistance has been recognized [14].…”
Section: Introductionmentioning
confidence: 99%
“…More encouragingly, probiotic supplements might be an assistant treatment strategy for these complications. A systematic review which included a total of 20 randomized controlled trials involving 2972 participants found that probiotic supplements had certain functions to reduce the level of fasting plasma glucose (FPG) and improve insulin, insulin resistance, and insulin sensitivity, especially for GDM and healthy pregnant women [13]. The long-term risk of growth-restricted fetuses is similar to that of offspring of women with GDM, and the role of insulin resistance has been recognized [14].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics have positive effects on preventing and alleviating diabetes by regulating the intestinal microenvironment and immunity (Liu et al, 2017). Probiotic therapy may be a promising approach to improve glucose control and insulin resistance among pregnant women (de Brito Alves et al, 2019;Pan et al, 2021). Previously, our results showed that Lactobacillus and Bifidobacterium probiotic supplements could reduce the fasting blood glucose level of GDM rats by restoring the diversity of gut microbiota (Zheng et al, 2021).…”
Section: Introductionmentioning
confidence: 83%
“…Notably, all of the included studies in our meta-analysis with significant decrease in the GDM incidence started supplementation before 20 weeks of pregnancy ( 20 , 27 , 32 ) while the studies by Asgharian et al and Lindsay et al which started after 20 weeks of pregnancy found no significant effect on the incidence of GDM ( 26 , 29 ). Furthermore, the dosage of intervention may influence the effect as 10 9 CFU/day or higher was suggested to be more efficient in lowering glucose markers ( 36 ) although all the studies included in our meta-analysis used more than 10 9 CFU. All three studies that found significant decline following probiotics used capsules for administration which is more feasible to achieve desirable and accurate dose ( 20 , 27 , 32 ).…”
Section: Discussionmentioning
confidence: 99%